2000
DOI: 10.1046/j.1462-2920.2000.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of two years of community dynamics in an anaerobic bioreactor using fluorescence polymerase chain reaction (PCR) single‐strand conformation polymorphism analysis

Abstract: The structures of the bacterial and archaeal communities in an anaerobic digester were monitored over a 2 year period. The study was performed on a fluidized bed reactor fed with vinasse. The objective was to characterize the population dynamics over a long time period under constant environmental parameters. Total bacterial and archaeal populations were measured independently by fluorescence-based polymerase chain reaction (PCR) single-strand conformation polymorphism (SSCP) analysis using an automated DNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(157 citation statements)
references
References 20 publications
9
144
2
2
Order By: Relevance
“…3), the maximum saturation of potential species was never achieved for phase 2 transitions from SBWW to acetate/sulfate and acetate alone. This is consistent with prior studies in bioreactors showing large increases in rare populations of bacterial species as the result of change or perturbation (Delbes et al, 2000(Delbes et al, , 2001Zumstein et al, 2000;Fernandez et al, 1999Fernandez et al, , 2000LaPara et al, 2002;Pender et al, 2004). Thus, the transient increase in diversity levels that was noted might be more reflective of the true complexity of bacterial populations within the structured biogranular communities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3), the maximum saturation of potential species was never achieved for phase 2 transitions from SBWW to acetate/sulfate and acetate alone. This is consistent with prior studies in bioreactors showing large increases in rare populations of bacterial species as the result of change or perturbation (Delbes et al, 2000(Delbes et al, , 2001Zumstein et al, 2000;Fernandez et al, 1999Fernandez et al, , 2000LaPara et al, 2002;Pender et al, 2004). Thus, the transient increase in diversity levels that was noted might be more reflective of the true complexity of bacterial populations within the structured biogranular communities.…”
Section: Discussionsupporting
confidence: 92%
“…The composition of the bacterial communities residing in biogranules depends on the waste being treated, but generally consists of two or three distinct trophic levels of organisms, such as fermentative organisms, fatty acid-oxidizing bacteria (syntrophs) and acetogenic bacteria (Schink, 1992a(Schink, , 1997Briones & Raskin, 2003). Past research has shown that UASB and other methanogenic reactors are extremely stable functionally (Fernandez et al, 1999;Zumstein et al, 2000;LaPara et al, 2002;Pender et al, 2004), but the underlying basis of the functional stability is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Total DNA from about 0.2 g of template was extracted with the QIAamp R DNA Stool Mini kit (Qiagem S. A., Courtaboeuf, France). The V3 region of 16S rRNA bacterial genes was amplified by PCR using the primers w49 and 5 0 -6FAM-labelled w34 (Delbè s et al, 1998;Zumstein et al, 2000). Amplicons were subjected to capillary electrophoresis singlestrand conformation polymorphism (CE-SSCP) as described by Michelland et al (2009a).…”
Section: Methodsmentioning
confidence: 99%
“…Ecological theories based on stochastic models and principles of island biogeography suggest that bioreactor community dynamics may be governed by chaotic shifts among functionally redundant organisms (6). In laboratory-scale systems, researchers have observed stable community structures in functionally stable (7) and unstable (8,9) bioreactors, community shifts that could be explained by reactor conditions (10,11), and even chaotic community shifts in functionally stable bioreactors (12,13). It is difficult to assess the observed discrepancies between stable communities and those that are more dynamic.…”
mentioning
confidence: 99%